Equívoco na recepção acadêmica da teoria de Emília Ferreiro - Gonçalves, Júnia Alba (2008)
This study tried to focus upon the academic reception which the psychogenetic theory of learning the written symbolic system had among the teachers in the schools of the fundamental level in Uberlândia. Emília Ferreiro directly, Jean Piaget and Lev Vigotski indirectly were brought into the scene as well. The research approach was qualitative and the instruments used in the research were the following: a questionnaire and an oral interview. The analysis of data shows that linguistic knowledge is vital in the task of teaching the written system and that the teachers usually have a misconception of Ferreiro's psychogenetic theory.